Influence of the moisture and ash content in flue gases on the performance of adsorption processes using activated carbons to capture the CO2 for reuse in greenhouses - R. López Pastor; M.G. Pinna-Hernández; J.A. Sánchez Molina; F.G. Acién Fernández (Heliyon)
This work studies the influence of flue gas composition, its moisture and ash content, on the efficiency of a CO2 adsorption/desorption process to capture the CO2 from flue gases along with its subsequent reuse in greenhouse CO2 enrichment (Patent ES2514090). The influence of the inlet flow rate, moisture, and ash content were analysed. The experimental conditions were based on those that are achievable under real operating conditions, namely an inlet flow rate from 1.2 to 4.8 L per minute, humidity from 3 % to 65 %, and an ash concentration from 0 % to 1 %. The results show that the inlet flow had no effect on the adsorption capacity but that there was a reduction in the adsorption capacity at the higher humidity and ash content levels studied, of 10.5 % and 21 %, respectively. The data were used to develop models based on the Langmuir and Freundlich isotherm that fitted the experimental data with a reliability of 100 % and 80.1 %, respectively. This model was used to optimize the combustion gas variables and thus their influence on the final CO2 adsorption/desorption capacity. The techno-economic analysis performed confirmed a total cost reduction of 12 % when using the optimal combustion gas conditions (a relative humidity of 3 % and an ash concentration of 0 %) versus the worst gas conditions (a relative humidity of 65 % and an ash concentration of 1 %), which resulted in a saving of 60 % by avoiding the use of liquified CO2. These results confirm the technical and economic viability of the proposed technology and its potential contribution to improving the environmental and economic sustainability of agricultural food production.